The Role of Disease Activity Score 28 in the Evaluation of Articular Involvement in Systemic Lupus Erythematosus. (3rd November 2014) - Ceccarelli, Fulvia; Perricone, Carlo; Massaro, Laura; Pacucci, Viviana Antonella; Cipriano, Enrica; Truglia, Simona; Miranda, Francesca; Spinelli, Francesca Romana; Alessandri, Cristiano; Valesini, Guido; Conti, Fabrizio
Abstract : Objectives . To evaluate the application of Disease Activity Score 28 (DAS28) to assess joint involvement in Systemic Lupus Erythematosus (SLE). Methods . Sixty-nine SLE patients, complaining of joint symptoms, and 44 rheumatoid arthritis (RA) patients were enrolled. In SLE patients disease activity was assessed with SLEDAI-2K. DAS28 was calculated in all the patients. Results . Thirty SLE patients (43.5%) showed clinical signs of arthritis. Mean DAS28 was 4.0 ± 1.4, 22 patients (31.9%) had low disease activity, 29 (42.0%) moderate, and 18 (26.1%) high. We dichotomized SLE patients according to the presence (Group 1) or absence (Group 2) of articular involvement according to SLEDAI-2K: 56.3% of the patients of the second group had a moderate/high activity according to DAS28. We compared SLE patients with 44 RA patients (M/F 9/35, mean age 55.6 ± 14.5 years; mean disease duration 140.4 ± 105.6 months). No significant differences were found regarding the values of DAS28 between SLE and RA patients. On the contrary, the values of tender and swollen joint count were significantly higher in RA compared to SLE patients (P = 0.0002 and P = 0.0001, resp.). Conclusions . We suggest the use of the DAS28 in the assessment of joint involvement in SLE patients.